Manajemen Risiko Operasional Pada PT Bank Pembiayaan Rakyat Syariah (BPRS) Jabal Nur Tebuireng di Surabaya - Jelita, Wienanda Rizka Sukma; Shofawati, Atina (Universitas Muhammadiyah Malang, 2019)
This study present to determine the management analysis of BPRS. This study was conducted at management that is different from the phenomenon that occurs in the object of research, namely PT BPRS Jabal Nur Tebuireng. This study uses qualitative methods with a case study approach. The way to manage the data is done by a focused open-ended method. The analysis technique used is matchmaking of patterns by comparing empirical patterns with predicted patterns. PT BPRS Jabal Nur Tebuireng has carried out operational management in accordance with ISO 31000 (2009). Possible conditions, but at the time of BPRS analysis Jabal Nur did not make a list of risks in which there was a Composite Risk Index (CRI) and made a matrix. In the evaluation phase, it was found that BPRS Jabal Nur Tebuireng were people involved in internal processes and fraud. So far BPRS Jabal Nur Tebuireng has been handling various operations.